„Szemináriumi Élet”: A pécsi növendékpapság Szent Pál Társulatának egyházirodalmi kiadványa (1921–1951) - Vértesi, Lázár (Per Aspera ad Astra, 2015)
The Episcopal Seminary of Pécs was a prominent intellectual workshop since 1746. It gave an intellectual background for all the future priest seminarists which was traditionally reach and was always ready to renew. It does not derive only from human qualities that the seminarists showed moral courage during historical changes and was able to organize the charity and endowment of the hinterland’s rural population during wartime or even that they stayed right at their parish with slandered so as to give relief and show solidarity and humanity. We shall find the roots of their attitude in the community they were brought up and where their identity and commitment were created. This alma mater was the seminary. The seminary founded by Zsigmond Berényi (1740–1748) was capable to an intellectual self-organization. The organizational frames of this were given by the Saint Paul Company established in 1865, which published the issue titled Szemináriumi Élet (Life in the Seminary) from 1921. Through the articles of the issue we can get a glance at the inwardness that was given by the teachers and the magistrates of this institution to the young clergymen. The thematic horizon of publications was determined by the dynamics of the inherent spiritual demands of the seminarists and the answers for the questions derive from the spirit of the age. The tones of the issues were driven by a special maturing process which was compatible to the changes resulted within the Hungarian Catholic Church’s scope for action. This paper tries to show these changes through the presentation of the columns, writers and editors, while it also tries to give insight to the basic moments of the history of the Hungarian Catholic Church between the two World Wars.